Mind, Body and Boundaries: Self-Presentation on the Nordic LGBTQ Online Dating Scene - Miller, Emelie Louise (Frontiers in Psychology, 2019)
Online dating is continually on the rise and nowadays a widely used and accepted way to find different kinds of companionship. This relatively new interpersonal phenomenon has provided an especially important virtual space for non-heterosexuals. Previous research on behaviors and trends on dating communities online for sexual minorities has focused primarily on sites for gay men in Anglo-Saxon countries. The purpose of the present study is to examine self-presentations on the Nordic LGBTQ online dating scene and possible gender-dependent differences in self-presentation. The Nordic countries are commonly perceived as progressive in issues regarding gender equality and LGBTQ rights. The countries on average also have low population density with large rural areas and consequently limited scenes for non-heterosexuals. A testimony of this is the study’s selected dating site, which is based in Sweden but encompasses the neighboring countries and markets itself as a Nordic meeting venue. The present study embarks on new territory within psychology-, gender-, and queer research by examining self-presentations on a mixed-gender LGBTQ dating site, situated in the supposedly liberal Nordic countries. Based on qualitative and quantitative data from a stratified sample of 716 cis-gendered, predominantly Swedish online dating profiles, on a well-established Nordic online dating site for non-heterosexual men and women, statistical calculations and a thematic analysis (TA) were executed. The findings show that central self-presentations concern mind versus body, lust and longings, and boundaries, where gender frequently functions as the dividing line. Women self-present more through personality and romantic longings compared to men, who to a higher degree emphasizes body, and lust. Self-presentation is also expressed through resistance against boundary-breaking contact on the site. The boundaries that are guarded regard age, anti-racism and most pronounced – boundaries against male harassment of non-heterosexual women. The implications of self-presentation, possible discrimination and misrepresentation on the Nordic LGBTQ online dating scene are discussed.